Factors Related to the Prevalenceof Chronic Kidney Disease in Indonesia:An Ecological Study - Achmad Yudi Arifiyanto; Agung Dwi Laksono; Djazuly Chalidyanto; Nungky Taniasari; Warih Kusumaningtyas (Indian Journal of Forensic Medicine & Toxicology, 2021)
Previous research has found that the cost of chronic kidney disease is relatively high. This study aims to ecologically analyze the factors relatedto the prevalence of chronic kidney disease in Indonesia.The research conduct ecological analysis using secondary data from the Ministry of Health of the Republic of Indonesia report in 2018. The study takes all provinces as samples. Apart from chronic kidney disease, four other variables analyzed as independent variables were the adherence to taking antihypertensive drugs, dedication to taking anti-diabetic drugs/injections, a habit of drinking soft drinks > 1 time/day, a habit of drinking energy drinks> 1 time/day. Data were analyzed usinga scatter plot.The results showed that the higher the percentage of adherence to taking antihypertensive drugs in a province, the higher the prevalence of chronic kidney disease. The higher the percentage of commitment to taking anti-diabetes medications/injections in a section, the lower the prevalence of chronic kidney disease. The higher the rate of drinking soft drinks>1 timea day, the higher the prevalence of chronic kidney disease. The higher the percentage of regular drinking energy drinks>1 timea day, the higher the prevalence of chronic kidney disease.The study concluded that five independent variables analyzed were related to Indonesia’s prevalence of chronic kidney diseases.